Self-Esteem and Tendency of Nomophobia in College Students - Lydia Indira; Priska Vivian Febiola; Sri Mulyani Nasution (Analitika, 2023)
Nomophobia is defined as the fear of not having anything to do with cell phones. Research shows various psychological factors are involved when someone uses a cell phone excessively, such as low self-esteem. This phenomenon seems to be increasing globally. Addictive behavior related to smartphone use can be considered as part of the broader Nomophobia construct. Excessive use of smartphones is also seen by students who are in the Z generation group and are said to be digital natives. In general, students who are in the age range of 18-22 have quite an extreme dependence on smartphones and digital information using the internet. Examining this phenomenon, this study aims to determine the relationship between self-esteem and the tendency of Nomophobia in college students. This research was conducted on students in East Bekasi with a total sample of 100 male and female students. The research method uses a quantitative approach with a correlational method. The results of the correlation test between self-esteem and Nomophobia tendencies in students in East Bekasi showed a Pearson Product Moment correlation coefficient of 0.069 with a two-tailed test at a confidence level of 0.05 (5%). This means that there is no significant relationship between self-esteem and the tendency of Nomophobia among students.